Microencapsulação de antioxidantes naturais de erva-mate (Ilex paraguariensis) com alginato de sódio - Bachi, Luana Regina (2023)
This study addressed the optimization of phenolic compound extraction from yerba mate by considering the influence of the solute-to-solvent ratio and solvent mixing percentage. The results highlight the relevance of these factors to the concentration of phenolic compounds in the extract. The assay with 5.5 g of yerba mate showed the highest concentration, 7593.42 mgAGE/100g of sample in the extract, while higher concentrations triggered solute precipitation and saturation, reducing extraction efficiency. The percentage of ethanol in the solvent mixture is also crucial. The assay with 60% ethanol resulted in 4661.73 mgAGE/100g, surpassing others. The physicochemical characteristics of the raw materials, extracts, and microcapsules were also analyzed. Moisture and pH showed significant differences among samples, with the moisture content of raw yerba mate (61.95%) notably higher than that of microcapsules (3.24% and 3.26%, respectively). The pH of raw yerba mate (5.57) did not differ significantly from that of the extract and microcapsules. The ash content of the microcapsules (3.22% and 3.77%) differed from that of raw yerba mate (5.03%). Water solubility varied between empty microcapsules and those with extract (3.89% and 13.81%, respectively), a relevant parameter for controlled release of active compounds. Colorimetric analysis revealed differences in L*, a*, and b* coordinates, demonstrating the influence of the extract on the color of microcapsules. Microcapsule morphology, observed using optical and scanning electron microscopy, indicated the efficacy of the encapsulation process, particularly highlighting the concentration of the extract in the core. Phenolic compounds and antioxidant capacities of the extracts and microcapsules were assessed. The extract exhibited higher phenolic compound content (6698.01 mgEAG/100g) and greater antioxidant activity by the FRAP method (3340.78 μmolFe2SO4/g) compared to microcapsules (775.14 μmolFe2SO4/g). This difference may be attributed to the encapsulation process, which affects the release times of the active compounds. FTIR analysis was used to identify the functional groups in the studied materials. The presence of distinct bands in the spectra suggested interactions between the extract and alginate components, indicating structural modifications after extract incorporation. In summary, the results emphasize the sensitivity of phenolic compound extraction to experimental parameters, influence of solvent percentage, and efficacy of encapsulation. Additionally, physicochemical and colorimetric analyses provided insights into the microcapsule characteristics, while FTIR analysis elucidated the molecular interactions. This information is vital for yerba mate-based product development, providing industrial insights into formulations with desirable properties and antioxidant potential.